Effect of Food on Balcinrenone/Dapagliflozin Pharmacokinetics and the Pharmacokinetics of Balcinrenone When Dosed with a P‐gp Inhibitor - Anna L. Eriksson; Deeyen Karsanji; Amy H. Shi; Joanna Parkinson; Maria Heijer; Edward Austin; Bosse Lindmark; Charlotta Vedin‐Nilsson; Judith Hartleib‐Geschwindner; Maria Leonsson‐Zachrisson; Hans Ericsson (The Journal of Clinical Pharmacology, 2026)
Abstract Balcinrenone (AZD9977) is a novel selective non‐steroidal mineralocorticoid receptor antagonist with a distinct mode of action being developed as a fixed‐dose combination with the sodium–glucose cotransporter‐2 inhibitor dapagliflozin for the treatment of heart failure with impaired kidney function, and chronic kidney disease. In this Phase 1 randomized open‐label three‐way crossover study we investigated the effect of food on balcinrenone/dapagliflozin pharmacokinetics, and the pharmacokinetics of balcinrenone when dosed with a P‐glycoprotein (P‐gp) inhibitor. Fourteen healthy participants were administered an oral capsule of balcinrenone/dapagliflozin 40 mg/10 mg in three dosing periods: fasted (reference), fed (high‐fat, high‐calorie meal) and with a P‐gp inhibitor (quinidine 300 mg × 2). Balcinrenone exposure was comparable in the fed and fasted states (geometric mean ratios [GMRs] [90% CI]: maximum plasma concentration [C max ] 1.05 [0.88, 1.25]; area under the plasma concentration–time curve from time 0 to infinity [AUC inf ] 1.12 [1.06, 1.19]). In the fed state, dapagliflozin AUC inf was comparable to the fasted state (GMR [90% CI] 1.05 [1.01, 1.09]), whereas C max was decreased (GMR [90% CI] 0.59 [0.51, 0.69]), in line with previous dapagliflozin food interaction studies. Co‐administration with quinidine increased balcinrenone exposure: GMRs (90% CI) 1.48 (1.24, 1.76) and 1.24 (1.17, 1.31) for C max and AUC inf , respectively, but AUC fold increase was